Zanesljivost volumenskih funkcij na primeru drevesne vrste smreke v Sloveniji - Kušar, Gal (Acta silvae et ligni, 2013)
Various volume functions used for tree volume estimations were compared by the authors. Using section measurements (Newton's method), they calculated the real tree volumes of 88 felled spruce trees on the Pokljuka plateau. The real tree volumes were used to form regional three-entry volume functions, (two-entry) volume tables, and tariff functions. The standard error of the average tree volume estimation is the lowest for three-entry volume functions (5.0%), then for volume tables (11.7%), and the highest for tariffs (15.1%). The reliability and applicability of the developed regional and other volume functions was verified on two one-hectare research plots. It was established that by applying the adapted German volume tables, the measured spruce volumes were too high. As the volumes measured in this manner are used when determining the adapted tariffs in Slovenia, this procedure results in a tariff class of at least 5% too high tree volumes.
Keywords: volumenske funkcije; volumen dreves; lesna zaloga; smreka; Picea abies; Pokljuka